Capital Adequacy Ratio, Third-Party Funds and Interest Rates Impact on Profitability - Muhammad Ja'far Shiddiq; Fazaalloh, Al Muizzuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The profitability of banks in the KBMI IV group, which dominates nearly half of Indonesia's banking assets, plays a crucial role in the stability and performance of the national financial system. This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Third-Party Funds (DPK), and Interest Rates on the profitability of KBMI IV banks in Indonesia using Return on Assets (ROA) as the profitability proxy. Employing a quantitative approach with panel data regression analysis from 2012 to 2022, the study used the Fixed Effect Model (FEM) as the optimal estimation technique. The findings show that CAR has no significant effect on ROA, DPK has a negative and significant effect, while Interest Rate positively and significantly affects ROA. Simultaneously, all three variables jointly influence profitability. These results suggest that having a large capital base or deposit fund alone is not sufficient to enhance bank performance unless accompanied by strategic allocation and efficient management. The implication is that banks need integrated financial strategies that balance risk, optimize capital use, and respond effectively to interest rate movements to ensure long-term profitability and financial resilience.